Crenças de professores de Libras na formação de tradutores e intérpretes - Rabelo, Waléria Cristine de Sousa Veiga (2021)
The theme of this paper is the beliefs of Brazilian Sign Language teachers (Libras) in the training of translators and interpreters in Libras-Portuguese. The research proposes to investigate and analyze the beliefs of university professors who teach Libras in a Bachelor's Degree course for training translators and interpreters at a federal public university. This study is based on authors who discuss language teaching and the role of beliefs in the field of language teaching and learning, such as Barcelos (2004, 2010), Borges (2017), Figueiredo (2015), Lago (2011) and also, translation and interpretation theorists, such as Nogueira and Santos (2018), Rodrigues (2019) and Faria and Galan-Mañas (2018). This investigation is characterized by being a mixed study, with an emphasis on exploratory research and a predominantly qualitative approach, using the interview technique as a data collection instrument. Data analysis is based on the content analysis technique (BARDIN, 2011), with the construction of categories and meaning cores. The data demonstrate the existence of beliefs about the teaching of Libras in the training of translators and interpreters, indicating that the teacher is required to: a) professional and linguistic profile (fluency, linguistic knowledge of the Libras modality and specificity of translation and interpretation); b) awareness (political and cultural about the deaf community); and c) didactics (in the relationship between teachers and students and in teacher self-assessment). It is concluded that the teachers' beliefs are many, that they are aware of them, and that beliefs change over time. The surveyed teachers realize that language teaching must be taught according to the target audience and that specific education is needed aimed at training the interpreter for an adequate performance in the use of the language, giving due importance to the act of translating and interpret. The data indicate that the respondents attach importance to the qualification of the teacher who teaches the language and importance to the qualification of the interpreter and are concerned with the teaching of Libras, in particular, with self-assessment, with the effectiveness of didactics in teaching, with the creation of differentiated didactic material and with the preparation of the classes taught, aiming at a good training of future interpreters and the search for an ideal method for teaching Libras. The research subjects demonstrate political commitment to support the deaf community, highlighting the belief that learning Libras and fluency in the language will happen, more effectively, through contact with the deaf and with the deaf community.